2016
DOI: 10.2224/sbp.2016.44.4.679
|View full text |Cite
|
Sign up to set email alerts
|

Gender Moderates Firms' Innovation Performance and Entrepreneurs' Self-efficacy and Risk Propensity

Abstract: On the basis of upper echelons theory and social learning theory, we examined the direct effects of 2 cognitive characteristics—self-efficacy and risk propensity—on entrepreneurs' innovation in the early stage of entrepreneurial activities. We also investigated the moderating role of gender on these relationships, using data collected from the 2011 Global Entrepreneurship Monitor database, comprising 12,828 entrepreneurs from 44 countries. We found that both self-efficacy and risk propensity were positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
2
10
0
5
Order By: Relevance
“…The literature on the gender of the entrepreneur confirms that gender moderates entrepreneurship [72,73], motives for entrepreneurship [74], and risk-taking in innovation [75]. With regards to the relationship between gender and innovation, previous studies found a weak but positive relationship, confirming that men are more innovative than women [68,69,76,77].…”
Section: Sociodemographic and Economic Variablesmentioning
confidence: 97%
“…The literature on the gender of the entrepreneur confirms that gender moderates entrepreneurship [72,73], motives for entrepreneurship [74], and risk-taking in innovation [75]. With regards to the relationship between gender and innovation, previous studies found a weak but positive relationship, confirming that men are more innovative than women [68,69,76,77].…”
Section: Sociodemographic and Economic Variablesmentioning
confidence: 97%
“…From a business perspective, entrepreneurial self-efficacy is described as an individual's belief in their capability to successfully carry out various roles and activities of an entrepreneur, such as developing new business ideas and creating new products or services [30,31]. Previous research has shown that entrepreneurial selfefficacy plays a vital role in creating an internal environment conducive to the growth of innovation [18,32,33]. Based on existing literature, the hypotheses proposed in this study were as follows: Hypothesis 3 (H3).…”
Section: The Role Of Entrepreneurial Self-efficacymentioning
confidence: 99%
“…Self-efficacy is a psychological and motivational construct related to people's beliefs in their abilities, talent and capabilities to trigger the motivation, course of action and cognitive resources to control events of their lives (Yu and Chen, 2016). Past studies stated that self-efficacy is the most dominant performance criterion, as self-efficacy is a strong internal motivation.…”
Section: Related Review and Hypothesis Developmentmentioning
confidence: 99%